UPAYA PENINGKATAN KEMANDIRIAN PANGAN DI PANTI ASUHAN PETERMAS MELALUI BUDIDAYA IKAN LELE SISTEM AKUAPONIK - Hasana, Imroatin; Ubaidillah, Muhammad Khoiri; Azzahra, Aufa Farra; Trisdayanti, Ike; Puspandari, Lely Ayu; Handajani, Hany (Jurnal Abdi Insani, 2024)
The community service activity involves empowering the community of students at the Petermas Orphanage through the cultivation of catfish using the Mutiara aquaponic system, aiming for food self-sufficiency. This activity is motivated by several issues, including the lack of nutritional needs in the form of animal and plant proteins, irregularity in donors, and limited entrepreneurial skills, leading to insufficient provisions. Additionally, there are unused and neglected concrete ponds due to the limited knowledge of the students and administrators regarding cultivation. The main goal of this program is to address all the challenges faced by the Petermas Orphanage. Furthermore, the program aims to enhance the skills and knowledge of students and administrators in aquaculture. This program is conducted offline and begins with awareness and training activities, the installation of aquaponic ponds, soaking and settling of cultivation water. Subsequently, catfish seed dispersal, aquaponic vegetable planting, and the construction of aquaponic frameworks take place. Following that, there is monitoring, aquaponic catfish harvesting, and activity evaluation. This community service project has achieved positive and satisfactory results. The harvest is highly satisfying, with fresh water spinach and pokcoy vegetables in good condition. The catfish, raised under these conditions, are of high quality and the appropriate size for consumption. One kilogram of catfish contains 7-8 fish, measuring between 20-30 cm, with a weight of 60-85 grams. The PKM-PM program can achieve food self-sufficiency, meet the needs for animal and plant protein, and create new entrepreneurship opportunities for the Petermas Orphanage.